2004
DOI: 10.2134/agronj2004.0997
|View full text |Cite
|
Sign up to set email alerts
|

Land Application of Oily Food Waste and Corn Production on Amended Soils

Abstract: strate for the soil microbial biomass and has the potential to be an agricultural soil amendment that provides Oily food waste containing high concentrations of fat, oil, and a beneficial source of organic matter. Higuchi and Kurigrease (FOG) is produced by the food service and food production/ processing industries. Fat, oil, and grease have a high C/N ratio (90:1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…Additionally, fertilizerderived N treatments were established to serve for comparison to the broccoli residue-derived N treatments. In incubation studies, mineral N is typically added to establish sufficient SMN levels for microbial decomposition, such as in Rashid and Voroney (2004). Thus, to investigate the timing of broccoli residue N mineralization in relation to the microbial N requirement for organic C decomposition, the fertilizer-derived N treatments included: fertilizer only (with 34 mg of NH 4 NO 3 ), 268 mg of dry broccoli residue '34 mg of NH 4 NO 3 , and 34 mg of NH 4 NO 3 'each OCA, at the respective, aforementioned rate.…”
Section: Nitrogen Mineralizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, fertilizerderived N treatments were established to serve for comparison to the broccoli residue-derived N treatments. In incubation studies, mineral N is typically added to establish sufficient SMN levels for microbial decomposition, such as in Rashid and Voroney (2004). Thus, to investigate the timing of broccoli residue N mineralization in relation to the microbial N requirement for organic C decomposition, the fertilizer-derived N treatments included: fertilizer only (with 34 mg of NH 4 NO 3 ), 268 mg of dry broccoli residue '34 mg of NH 4 NO 3 , and 34 mg of NH 4 NO 3 'each OCA, at the respective, aforementioned rate.…”
Section: Nitrogen Mineralizationmentioning
confidence: 99%
“…(1 fresh organic carbon material and within the recommendations set by Rashid and Voroney (2004) for used cooking oil. The amounts of wheat straw, yard waste, and used cooking oil can be expressed as quantities of added C, with C loading rates of 1.2, 0.9, and 1.5 g C kg…”
Section: Nitrogen Mineralizationmentioning
confidence: 99%
“…Unlike sewage sludge and many other organic amendments which can contain significant amounts of N, phosphorus, potassium, or other nutrient materials, GTW contains large amounts of readily degradable C compounds but very little of the nutrients required for plant or microbial growth (Rashid and Voroney 2004); thus, this may lead to an imbalance in C and other essential nutrients creating negative effects on soil bacterial community. Evidently, our results have major implications for developing sound regulatory guidelines for the use of GTW in agriculture by indicating which types of GTW are unsuitable for application in the agricultural soils due to their significant negative effects on soil bacterial community.…”
Section: Effects Of Organic Wastes On Soil Bacterial Communitymentioning
confidence: 99%
“…Soil 1 Background, aim, and scope Grease trap waste (GTW) is an organic waste collected and pumped out of grease traps in wastewater drains in restaurant areas in cities to reduce the concentration of fat and suspended solids in the wastewater. Because the potential benefit of GTW as a source of organic matter and soil conditioner containing no/low amounts of metals or pathogenic organisms (Rashid and Voroney 2004), current Australian legislation permits the beneficial application of the GTW into agricultural soil. However, little is known about the influence of GTW on soil bacterial community.…”
mentioning
confidence: 99%
“…Research has demonstrated that SMN concentrations may be reduced via N immobilization by the applications of wheat straw [19][20][21], yard waste [22][23][24], and oily food waste [16,25,26]. In the aforementioned studies, immobilized N was derived from fertilizers or indigenous SMN.…”
Section: Introductionmentioning
confidence: 99%